Competitive warm-up in basketball: literature review and proposal - Daniel Berdejo- (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract Warm-up is used, accepted and performed by every participant before practising any sport. Warm-up is also considered by most sportmen as fundamental to achieve optimal performance. However, there is little scientific evidence supporting its effectiveness. This lack of evidence, together with the diversity of sports, requires the standardisation of common warm-up patterns for each sport activity. As elite basketball is concerned, a large scientific gap has been found, which the present article will attempt to fill in. Therefore, the objectives of this paper are: first, conducting a literature review on all aspects of warm-up, i.e. warm-up definition, warm up types, warm-up benefits, warm-up structure (intensity, duration, recovery and specificity), influential factors, as well as what kind of stretching must be included in the warm-up; and secondly, from the conclusions obtained,  describing and proposing a methodology which is adapted to competitive warm-up for high-level basketball, so this methodology serves as a justified reference guide when going through the pre-game phase. Key Words: static stretching, dynamic stretching, generic warm-up, specific warm-up, basketball.